Faktor Faktor Stress Teknologi Yang Mempengaruhi Kesalahan Data Rekam Medis Elektronik - Greace Ana Maria Banda Rarong; Didik Setyawan; Sugiarmasto sugiarmasto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Background: Errors in inputting medical record data are still found in health services. The phenomenon that occurs in the use of electronic medical records is still an obstacle for health workers due to the complexity of the system. So research to reduce errors in inputting electronic medical record data needs to be done. Aims: This study was conducted to examine errors in inputting medical record data. The error of medical record data is influenced by technological stress factors. In addition, technological stress which is a mediator variable is also influenced by three factors, namely technology that is realistically more advanced, compatibility and complexity. Methods: . Information collected through questionnaires distributed to health workers who meet certain criteria and using electronic medical records. A total of 200 individuals in the sample were selected, selected using nonprobability sampling techniques. To test the validity of the Strucktural Equation Model (SEM) Analysis used with the Amos method Results: The results of data analysis in this study show that technological stress has a positive impact on electronic medical record data errors. In addition, relatively more advanced technology and complexity also positively affect technology stress and compatibility negatively affect technology stress Conclusion: The application of technology for hospital administration must be easy to use without the need for more learning and compatibility between work, technology used, and people who use it to reduce stress on technology in order to facilitate the input of medical records.